Prevalence of islet autoantibodies in Thai juvenile‐onset type 1 diabetes. Issue 11 (22nd November 2018) - Trisorus, Chayanis; Aroonparkmongkol, Suphab; Kongmanas, Hataichanok Bansiddhi; Sahakitrungruang, Taninee
Abstract: Background: Type 1 diabetes mellitus (T1DM) is caused by autoimmune destruction of islet β‐cells of the pancreas. There are overlapping phenotypes in a significant proportion of youth with type 1 and 2 diabetes. Thus, positive pancreatic autoantibodies are helpful to diagnose T1DM. Zinc transporter 8 antibody (ZnT8A) is a recently identified autoantibody in T1DM and no data on ZnT8A in the Thai population have been reported. The aim of this study was therefore to estimate the prevalence of ZnT8A in Thai juvenile‐onset T1DM and to evaluate its diagnostic value relative to glutamic acid decarboxylase and insulinoma‐2 antigen antibodies (GADA and IA2A). Methods: In this cross‐sectional study, patients with T1DM diagnosed before age 15 years, and disease duration <10 years were enrolled. Serum ZnT8A, GADA, and IA2A were measured using commercial enzyme‐linked immunosorbent assay kits. Results: The subjects consisted of 81 youths (30 boys, 51 girls) aged 12.3 ± 4.5 years with T1DM. The median diabetes duration was 3 years (range, 0–10 years). The prevalence of ZnT8A, GADA, and IA2A was 54.3%, 75.3%, and 45.7%, respectively. ZnT8A were detected in 16% of T1DM patients negative for both GADA and IA2A. A combination of ZnT8A, GADA and IA2A could detect 80.2% of patients with T1DM. Combined use of ZnT8A and GADA identified 100% of antibody‐positive patients. Conclusion: The prevalence of ZnT8A in Thai juvenile‐onset T1DM appears to be higher than in previous studies from Asia. ZnT8A could replace IA2A as an autoimmunity marker in Thai pediatric T1DM patients, with better diagnostic performance.